RESPONSES OF POTATO PLANTLETS TO GROWING MEDIA AND MS CONCENTRATIONS DURING ACCLIMATIZATION - Lia Hamdiah; Susiyanti; Sri Ritawati; Sulastri Isminingsih (Gunung Djati Conference Series, 2026)
Potato plantlet acclimatization is a critical stage that determines plant survival and growth after transfer from in vitro to ex vitro conditions. The selection of suitable growing media and nutrient supply is important to support plantlet adaptation and development during this stage. This study aimed to evaluate the growth responses of potato plantlets to different growing media and Murashige and Skoog (MS) medium concentrations during acclimatization. The experiment was conducted at the Agroecology Laboratory, Faculty of Agriculture, Universitas Sultan Ageng Tirtayasa, from December 2025 to February 2026. A split-plot design was used with two factors. The main plot consisted of growing media, namely rice husk charcoal, cocopeat, and perlite, while the subplot consisted of MS medium concentrations of 0, ¼, ½, and 1 MS. Each treatment was replicated three times. Growth observations included plant height increment, number of leaves, and number of shoots. Data were analyzed using analysis of variance followed by Duncan’s Multiple Range Test at the 5% level when required. Cocopeat produced the highest plant height increment at 6 weeks after transplanting, reaching 1.78 cm. Plantlets supplied with 1 MS medium concentration produced the highest number of leaves at 3 weeks after transplanting, with 2.60 leaves, and the highest number of shoots at 5 weeks after transplanting, with 0.56 shoots. The results indicate that plantlet growth during acclimatization was influenced by both the physical properties of the growing media and nutrient availability. The use of cocopeat and an adequate MS medium concentration can therefore be considered to support potato plantlet growth and improve acclimatization performance under ex vitro conditions.